A 5-year-old boy with super-refractory status epilepticus and RANBP2 variant warranting life-saving hemispherotomy - Straka, Barbora; Koblížek, Miroslav; Splítková, Barbora; Valkovičová, Radka; Krsková, Lenka; Kalinová, Markéta; Vlčková, Markéta; Zámečník, Josef; Laššuthová, Petra; Sedláčková, Lucie; Staněk, David; Maulisová, Alice; et al. (Epilepsia open, 2024)
Focal cortical dysplasia (FCD) represents the most common cause of drug-resistant epilepsy in adult and pediatric surgical series. However, genetic factors contributing to severe phenotypes of FCD remain unknown. We present a patient with an exceptionally rapid development of drug-resistant epilepsy evolving in super-refractory status epilepticus. We performed multiple clinical (serial EEG, MRI), biochemical (metabolic and immunological screening), genetic (WES from blood- and brain-derived DNA), and histopathological investigations. The patient presented 1 month after an uncomplicated varicella infection. MRI was negative, as well as other biochemical and immunological examinations. Whole-exome sequencing of blood-derived DNA detected a heterozygous paternally inherited variant NM_006267.4(RANBP2):c.5233A>G p.(Ile1745Val) (Chr2[GRCh37]:g.109382228A>G), a gene associated with a susceptibility to infection-induced acute necrotizing encephalopathy. No combination of anti-seizure medication led to a sustained seizure freedom and the patient warranted induction of propofol anesthesia with high-dose intravenous midazolam and continuous respiratory support that however failed to abort seizure activity. Brain biopsy revealed FCD type IIa; this finding led to the indication of an emergency right-sided hemispherotomy that rendered the patient temporarily seizure-free. Postsurgically, he remains on antiseizure medication and experiences rare nondisabling seizures. This report highlights a uniquely severe clinical course of FCD putatively modified by the RANBP2 variant. PLAIN LANGUAGE SUMMARY: We report a case summary of a patient who came to our attention for epilepsy that could not be controlled with medication. His clinical course progressed rapidly to life-threatening status epilepticus with other unusual neurological findings. Therefore, we decided to surgically remove a piece of brain tissue in order to clarify the diagnosis that showed features of a structural brain abnormality associated with severe epilepsy, the focal cortical dysplasia. Later, a genetic variant in a gene associated with another condition, was found, and we hypothesize that this genetic variant could have contributed to this severe clinical course of our patient.
Keywords: Epilepsy; refractory status epilepticus; epilepsie; Humans; Brain Diseases; molekulární chaperony; dítě; Disease Progression; Midazolam; Child; Drug Resistant Epilepsy; Nuclear Pore Complex Proteins; status epilepticus; lidé; epilepsy surgery; focal cortical dysplasia; Molecular Chaperones; DNA; nemoci mozku; předškolní dítě; Focal Cortical Dysplasia; refrakterní epilepsie; midazolam; Male; RANBP2; hemispherotomy; komplex proteinů jaderného póru; progrese nemoci; Status Epilepticus; mužské pohlaví; Child, Preschool; fokální kortikální dysplazie